Optimizing Vocabulary Mastery Among Elementary Students Through the Baamboozle Application - Kosim, Nanang; Ardiansyah, Ade Arip; Rohmah, Alya; Rahmadina, Annida; Jannah, Atia Zahratul; Alpayed, Dody; Aziz, Dzulkifli (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2025)
This study was motivated by low Arabic vocabulary (mufradat) mastery among third-grade students of SD Ar-Rafi JOY in Kiaracondong, Bandung. This research aimed to improve students’ vocabulary acquisition using the interactive learning application Baamboozle. This study employed Classroom Action Research (CAR), consisting of two cycles: planning, implementation, observation, and reflection. The research subjects were 27 students. The findings showed a significant improvement in students' learning outcomes. In Cycle I, the average pre-test score was 50.59, which increased to 64.04 in the post-test. In Cycle II, the average pre-test score rose to 80.50, while the post-test reached 96.96. These results indicate that the use of Baamboozle was effective in enhancing students’ mastery of Arabic vocabulary. The interactive and engaging features of the application contributed to increased student motivation and participation in the learning process. This research suggests that digital media such as Baamboozle can be valuable tools for developing more attractive and effective Arabic language instruction. Future studies are recommended to explore the use of Baamboozle in improving other Arabic language skills, including speaking (kalām), listening (istimā‘), reading (qirā’ah), and writing (kitābah).